1974
DOI: 10.1039/f29747000356
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structures of metal complexes containing the π-cyclopentadienyl and related ligands. Part 2.—He I photoelectron spectra of the open-shell metallocenes

Abstract: He I photoelectron spectra are reported for the metallocene species ( C5H&V, (C,H,),Cr, (C5H&Mn, ( C S H 5 ) 2 C ~ and (C5H5)2Ni, and for their 1,l'-dimethyl derivatives. The metal 3d ionisation structure is discussed in terms of ligand field theory. The unusual spectrum of (CSH4Me)2 Mn is interpreted in terms of a high-spin/low-spin equilibrium in the gas phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
68
0
1

Year Published

1979
1979
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(79 citation statements)
references
References 0 publications
10
68
0
1
Order By: Relevance
“…7 The gas phase electron diffraction data of (MeC 5 H 4 ) 2 Mn have been interpreted as consisting of two monomeric spin isomers, where the ratio of high-spin (Mn-C(ave)= 2.43 Å) to lowspin (Mn-C(ave)= 2.14 Å) is 60:40 at 100 °C. 8,9 This gas phase structural study supports the deductions of earlier gas phase photoelectron spectroscopy (PES) studies that (MeC 5 H 4 ) 2 Mn is a spin equilibrium molecule in gas phase while Cp 2 Mn exists predominantly as the high-spin isomer. 10 The EPR studies of Ammeter and Maki have shown that Cp 2 Mn and (MeC 5 H 4 ) 2 Mn in frozen solution and doped in a host matrix of Cp 2 M or (MeC 5 H 4 ) 2 M (M= Mg, Fe), respectively, behave as spin crossover molecules, where a low-spin (LS) state is stabilized by about 0.5 kcal mol -1 .…”
Section: Introductionsupporting
confidence: 82%
“…7 The gas phase electron diffraction data of (MeC 5 H 4 ) 2 Mn have been interpreted as consisting of two monomeric spin isomers, where the ratio of high-spin (Mn-C(ave)= 2.43 Å) to lowspin (Mn-C(ave)= 2.14 Å) is 60:40 at 100 °C. 8,9 This gas phase structural study supports the deductions of earlier gas phase photoelectron spectroscopy (PES) studies that (MeC 5 H 4 ) 2 Mn is a spin equilibrium molecule in gas phase while Cp 2 Mn exists predominantly as the high-spin isomer. 10 The EPR studies of Ammeter and Maki have shown that Cp 2 Mn and (MeC 5 H 4 ) 2 Mn in frozen solution and doped in a host matrix of Cp 2 M or (MeC 5 H 4 ) 2 M (M= Mg, Fe), respectively, behave as spin crossover molecules, where a low-spin (LS) state is stabilized by about 0.5 kcal mol -1 .…”
Section: Introductionsupporting
confidence: 82%
“…1) at 9.0 ± 0.2 eV (peak B), 12.7 ± 0.2 eV (peak C), and 17.3 ± 0.2 eV (peak D) as well as the much weaker features at 0.9 ± 0.2 eV (peak A′) and 5.1 ± 0.2 eV (peak A″) are similar in relative intensities and binding energies to those assigned to cobaltocene adsorbed on cleaved graphite [32]. There is also a strong similarity between the gas phase photoemission spectra of cobaltocene [36][37], but with a shift of about 4 eV in the energy scale, as is typical of metallocenes [13][14][15], [17], [20][21][22][23], and [32], even though the moleculesubstrate as well as intermolecular interactions may shift, or broaden the molecular orbitals.…”
Section: Cobaltocene Adsorption On Cu(1 1 1)supporting
confidence: 54%
“…The big difference among these three metallocenes appears to be that the "nineteen electron" cobaltocene has a single unpaired electron resulting in a low ionization potential [32] of 5.56 eV [37] when compared to ferrocene (6.88 eV [37]) and nickelocene (6.51 eV [37]). This results in formation of a surface species that somewhat resembles [Co(Cp) 2 ] + on graphite [32] but apparently leads to fragmentation on Cu (1 1 1).…”
Section: The Stability Of Adsorbed Cobaltocenementioning
confidence: 99%
See 1 more Smart Citation
“…(1) and its 1,l '-dimethyl substituted derivative (-q5-C5H4CH3),Mn (2) (3)(4)(5). Moreover, the electronic state associated with the other possible 1s configuration, e;,ai,, or 'A,, state, is generally considered too far above the ground state energy level to be significantly populated or involved in a multiple ground state cross-over exchange process (6).…”
Section: Introductionmentioning
confidence: 99%